2017
DOI: 10.3389/fchem.2017.00033
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of CMC-g-PAM Superporous Polymer Monoliths via Eco-Friendly Pickering-MIPEs for Superior Adsorption of Methyl Violet and Methylene Blue

Abstract: A series of superporous carboxymethylcellulose-graft-poly(acrylamide)/palygorskite (CMC-g-PAM/Pal) polymer monoliths presenting interconnected pore structure and excellent adsorption properties were prepared by one-step free-radical grafting polymerization reaction of CMC and acrylamide (AM) in the oil-in-water (O/W) Pickering-medium internal phase emulsions (Pickering-MIPEs) composed of non-toxic edible oil as a dispersion phase and natural Pal nanorods as stabilizers. The effects of Pal dosage, AM dosage, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Ikem et al (2010b, 2011) have reported that introducing a small amount of surfactant (~5% of the continuous phase volume) to stabilize Pickering HIPEs cooperatively with particles before polymerization will reduce the void sizes of the poly-Pickering HIPEs and results in materials with large pore throats and permeability. Otherwise, the permeability and connectivity of the poly-MIPEs can be adjusted by changing the content of nanoparticles or introducing an appropriate amount of surfactant (Wang et al, 2017a,b). According to the preceding discussion, in this study, we reported a new strategy for fabrication of macroporous material from Pickering-MIPEs, which is stabilized by montmorillonite (MMT) together with nonionic surfactant, and non-toxic low-cost flaxseed oil was used as emulsion in disperse phase.…”
Section: Introductionmentioning
confidence: 99%
“…Ikem et al (2010b, 2011) have reported that introducing a small amount of surfactant (~5% of the continuous phase volume) to stabilize Pickering HIPEs cooperatively with particles before polymerization will reduce the void sizes of the poly-Pickering HIPEs and results in materials with large pore throats and permeability. Otherwise, the permeability and connectivity of the poly-MIPEs can be adjusted by changing the content of nanoparticles or introducing an appropriate amount of surfactant (Wang et al, 2017a,b). According to the preceding discussion, in this study, we reported a new strategy for fabrication of macroporous material from Pickering-MIPEs, which is stabilized by montmorillonite (MMT) together with nonionic surfactant, and non-toxic low-cost flaxseed oil was used as emulsion in disperse phase.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters of the isotherm models were summarized in Table 3. The Langmuir model was more better than the Freundlich model for describing the adsorption data of PhGs on CMK-3, which indicated that the adsorption of the PhGs on the CMK-3 was a simple monolayer adsorption process (Wang F. et al, 2017). In addition, the presence of oxygen-containing functional groups on the surface of CMK-3 enhanced the adsorption of PhGs.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, macroporous carboxymethyl cellulose-g-poly(acrylamide)/montmorillonite (CMC-g-PAM/MMT) monolith was prepared based on Pickering MIPEs, which stabilized with 5% of Mt and 4% of Tween-20 (Wang et al 2017). The obtained monolithic polymers were washed with acetone for 12 h and then immersed into 0.5 M NaOH aqueous alcohol solution (V water /V alcohol = 3/7) for 24 h to transfer the amide group to carboxyl.…”
Section: Methods and Approachesmentioning
confidence: 99%